Potential Impact of COVID-19 Outbreak on Education, Staff Development and Training in Africa - K. Ceesay Ebrima (International Journal of Coronaviruses, 2020)
Purpose This paper assess the impact of COVID-19 pandemic on Education, Staff development and Training in Africa. Online Research Methodology/Approach The data use in this paper was generated from online survey questionnaire, in which the participants were asked about certain questions in which covid-19 affect their social-economic situation. The questionnaire was design to help Africa to understand covid-19 impacts on their social and economic live. Results The results of this study reveal that coronavirus pandemic affected Africa in a number of ways; 1) 52.2 percent of the respondents said they should open school now in Africa, while 47.8 percent fear they should not open schools 2) 81 percent said before educational institution are closed there is public or official announcement that institutions must be closed due to pandemic—may be 3 months, ……,,…,, one week it depends on the severity of how covid-19 is spreading across the regions in Africa, 10.7 percent of the respondent said it may be and only 8.3 percent said it is not official announced.3) 65.4 percent of the respondents said government implemented an education response for continue of learning in Africa while educational institutions are closed 4) 61.5 percent said use of online/digital learning platform is the method for continuity of learning is currently available for children affected by closures of educational institutes provided by government, while 50 percent said television, radio, or podcast broadcast and 17.9 percent said assigning reading and exercises for home study. 5) 45.3 percent out of 100 percent said use of online or digital learning platform are the proportion of children affected by education institution closure. 38.7 percent said the proportion of children affect are the one that concentrate of using television, radio or podcast broadcasts to get academic content. 14.7 percent of the respondents are the proportion of the children affected by educational institute closure if they are assigning reading and exercises for home study. 6) 52.6 percent of the respondents from non-government organization, private schools said use of online or digital learning platform is the method for continuity of learning is currently available for children affected by closures of educational institutes, while 61.5 percent said use of online/digital learning platform is the method for continuity of learning is currently available for children affected by closures of educational institutes provided by government. The same thing government said as well. Similar respondents from government as do the non-government or private schools and 35.9 percent respondent said television, radio and podcast broadcast are method for continuity of learning is currently available for children affected by closures of educational institutes-provided by non-governmental organization, private schools etc, whereas 50 percent of the respondents said assigning reading and exercises for home study is the method for continuity of learning is currently available for children affected by closures of educational institutes-provided by government.7) 48.1 percent of the respondents said for the impact of covid-19 pandemic on staff development and training that their enterprise or organization partially suspended operation due to the pandemic and 34.2 percent of the responded said they completely suspended operation because of coronavirus pandemic and 16.5 percent said no closures on in operation for staff development and training because of pandemic. 8)According to the results of this question of the online survey, 49.3 percent said the challenges their enterprise face in delivery staff training programmes and activities using online learning or offline learning during covid-19 was due to infrastructure issues such the problem associated with internet and the like. The survey of the study also confirmed that 32.9 percent twice said limited digital skills of trainers and cost of staff training was a major setback to train staff in their enterprise or organization or department or establishment while 30.1 percent said it is due to limited digital literacy of users are the main challenges face by their department in order to train staff. Policy Implications The implication of the results from this online survey is that it has serious impacts on education closure and staff development and training. As educations are closed due to covid-19 pandemic, it will affect already problems of human capital that are hampering the development of Africa. Due to covid-19 pandemic, the achievement of sustainable development goals on quality education will be seriously halted. The government and the ministry in Africa should work hand in hand to solve the problems of children affected by schools closure after the pandemic by either additional hours or provide more study hours for schools to catch-up with what happened during the pandemic, the study noted. Originality/value The impact of covid-19 on education, staff development and training.
Keywords: Africa